2020
DOI: 10.3390/pharmaceutics12100964
|View full text |Cite
|
Sign up to set email alerts
|

Microbubbles and Nanobubbles with Ultrasound for Systemic Gene Delivery

Abstract: The regulation of gene expression is a promising therapeutic approach for many intractable diseases. However, its use in clinical applications requires the efficient delivery of nucleic acids to target tissues, which is a major challenge. Recently, various delivery systems employing physical energy, such as ultrasound, magnetic force, electric force, and light, have been developed. Ultrasound-mediated delivery has particularly attracted interest due to its safety and low costs. Its delivery effects are also en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 94 publications
(112 reference statements)
0
70
0
Order By: Relevance
“…Ultrasound targeted MBs destruction (UTMD) is an emerging method for delivering target genes into cells or living animal organs. It has become a research hotspot due to its advantages of simplicity, non-invasiveness, targeting and reproducibility ( 37 39 ). Low-frequency ultrasound has little effect on the biological interaction between healthy cells and normal tissue and is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound targeted MBs destruction (UTMD) is an emerging method for delivering target genes into cells or living animal organs. It has become a research hotspot due to its advantages of simplicity, non-invasiveness, targeting and reproducibility ( 37 39 ). Low-frequency ultrasound has little effect on the biological interaction between healthy cells and normal tissue and is safe.…”
Section: Discussionmentioning
confidence: 99%
“…FUS irradiation of a targeted region of the brain and the presence of MBs in the blood cause the transient disruption of the BBB, leading to promoting the permeation of nanoparticle through the BBB. Several reports demonstrated that FUS and MBs can be utilized to deliver therapeutic genes for curing neurodegenerative disease, especially in a PD mouse model [ 264 , 265 , 266 , 267 , 268 , 269 ]. There is strong evidence to show that neurotrophic factor can promote the regeneration of dopaminergic neurons to releive the PD syndrome [ 270 , 271 , 272 ].…”
Section: Non-viral Brain Targeting By Non-invasive Methodsmentioning
confidence: 99%
“…22 Transcutaneous ultrasound has been proven to be efficient for the delivery of genetic material to the liver of mice and pigs. 23,24 So far, the use of these approaches in liver-directed gene therapy is still restricted to experimental animal studies.…”
Section: Administration Of Naked Genetic Materialsmentioning
confidence: 99%